The Analysis of Difficulties in Implementing Learning Models in Islamic Education Teachers - Muhammad Polem; Septia Nur Saputri; Dian Nupus; Chaerul Rochman; Karman Karman; Asep Nursobah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
Abstract: Analysis of Difficulties in Implementing Learning Models in Islamic Education Teachers.The purpose of the study was to analyze the difficulties of Islamic Religious Education teachers in implementing learning models based on the Education Unit Accreditation Instrument (IASP 2020), including PBL, PjBL and Cooperative Learning learning models.This research uses the literature study method. Data analysis uses descriptive-qualitative starting with inventorying, classifying, and analyzing data.The results showed that the difficulties of Islamic religion teachers in applying learning models were caused by (1) mastery and application of learning models; (2) organizing and guiding students; (3) limited learning time.The conclusion of the research describes that Islamic religion teachers experience varied difficulties in implementing learning models that are in accordance with IASP 2020 and are caused by minimal school facilities and infrastructure.The results of this study can be a basis for consideration, as well as a contribution of thought for Islamic religion teachers, especially in designing effective and interesting learning.Abstrak: Analisis Kesulitan Implementasi Model Pembelajaran pada Guru Pendidikan Agama IslamTujuan penelitian untuk menganalisis kesulitan guru Pendidikan Agama Islam dalam mengimplementasikan model pembelajaran berdasarkan Instrumen Akreditasi Satuan Pendidikan (IASP 2020), meliputi model pembelajaran PBL, PjBL dan Cooperative Learning. Penelitian ini menggunakan metode studi Pustaka. Analisis data menggunakan deskriptif-kualitatif dimulai dengan menginventarisasi, mengklasifikasi, dan menganalisis data. Hasil penelitian menunjukkan kesulitan guru agama Islam dalam menerapkan model pembelajaran disebabkan oleh (1) penguasaan dan penerapan model pembelajaran; (2) mengorganisir dan membimbing siswa; (3) waktu pembelajaran yang terbatas. Kesimpulan penelitian mendeskripsikan bahwa guru agama Islam mengalami kesulitan yang bervariasi dalam mengimplementasikan model pembelajaran yang sesuai dengan IASP 2020 dan disebabkan oleh sarana dan prasarana sekolah yang masih minim. Hasil penelitian ini dapat menjadi dasar pertimbangan, serta sumbangan pemikiran bagi para guru agama Islam khususnya dalam mendesain pembelajaran yang efektif dan menarik.